A COMPARATIVE STUDY OF DCT AND DWT IMAGE COMPRESSION TECHNIQUES COMBINED WITH HUFFMAN CODING - Ashraf Maghari (Jordanian Journal of Computers and Information Technology, 2019)
Image compression techniques have been widely used to store and transmit data which requires storage space and high transfer speed. The explosive growth of high-quality photos leads to the requirement of efficient technique to store and exchange data over the internet. In this paper, we present a comparative study to compare between the Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) algorithms in combination with Huffman algorithm; DCT-H and DWT-H. The comparison is based on five factors: Compression Ratio (CR), Mean Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index Measure (SSIM) and compression/decompression time. The experiments are conducted on five BMP gray-scale file images. We found out that DWT-H coding is comparable to DCT-H coding in term of CR and outperforms DCT-H in terms of MSE, PSNR and SSIM. The CR average results of the five test images for DCT-H and DWT-H are 2.36 and 3.17, respectively. Moreover, DCT-H has the average results of MSE = 13.19, PSNR = 37.15 and SSIM = 0.76, while WDT-H has the average results of MSE = 4.54, PSNR = 42.5 and SSIM = 0.85. On the other hand, DCT-H outperforms DWT-H in term of execution time for compression and decompression. DCT-H has an average compression time of 0.358s and an average decompression time of 0.122s, while WDT-H has 2.38s compression time and 2.13s decompression time.